A Critical Investigation into Tyre Life on an Iron Ore Haulage System - G. C. Lindeque (The Southern African Institute of Mining and Metallurgy, 2016)
"A downward trend in tyre life on haul trucks at an open pit iron ore mine prompted an investigation into the current tyre management strategy in order to improve tyre life. ‘Best practice’ was compared to the current tyre management strategy at the mine to determine aspects that could be improved. Aspects that showed significant room for improvement included employee tyre awareness, tyre pressure maintenance, and road conditions. For each of these aspects a plausible alternative was suggested.A new tyre management strategy was formulated as a step-by-step guide on how to implement the proposed changes. Each step introduces new initiatives but at the same time builds on the previous step’s success. A sensitivity analyses was performed to determine the impact of the proposed changes, with the variables being the reduction in the percentage of premature tyre failure, and the reduction of the site wear rate.The ‘most likely’ scenario showed an increase in tyre life of 41% for the Komatsu 730 trucks and 105% for the CAT 777 trucks if the entire tyre management model is implemented. This would result in a possible annual saving related to tyre usage of R9.2 million. OverviewThe study focused on the tyre life on the main haul fleet at an open pit iron ore mine. The haul fleet consisted of 17 Komatsu 730 (180 t) haul trucks and 12 CAT 777 (90 t) haul trucks.The haulage operation consists entirely of tyre-based haul trucks. Five per cent of the total mining budget is related to tyre costs. Since 2012 there has been a steady decrease in tyre life as measured in operating hours (Figure 1) due to the high percentage of tyres that fail prematurely. In 2014 a total of 41% of all tyres failed prematurely and 61% were classified as ‘worn out’."